Overview: Model predictive control techniques for controlling induction motor based on vector control - Alakkad, Moataz M.A.; Talib, Md. Hairul Nizam; Rasin, Zulhani; Mat Lazi, Jurifa; Md. Jamal, Muhammad Haziq; Mat Isa, Zainuddin (Institute of Advanced Engineering and Science, 2024)
This paper presents a comprehensive review of electric induction motor (IM) drive systems. It conducts an evaluation and critical analysis of modern control techniques aimed at enhancing induction motors or IM drive performance, drawing insights from a systematic literature survey. This review paper introduces the mathematical and dynamic models of induction motors and control via two-level inverter drives. Furthermore, the paper offers an extensive review of model predictive control (MPC) for induction motors which is considered a vector control (VC) technique. The MPC are subdivision based on control parameters into two modes, model predictive current control (MPCC) and model predictive torque control (MPTC). The paper thoroughly examines each control technique, providing insights into mathematical control analysis, block diagrams, and operational mechanisms, as well as the advantages and disadvantages associated with the method. The model predictive control (MPC) stands out due to its distinct advantages, particularly in terms of simplicity, accuracy, and efficiency.